Brain ageing changes proteoglycan sulfation, rendering perineuronal nets more inhibitory - Foscarin, Simona; Raha-Chowdhury, Ruma; Fawcett, James W; Kwok, Jessica C F (Aging, 2017)
Chondroitin sulfate (CS) proteoglycans in perineuronal nets (PNNs) from the central nervous system (CNS) are involved in the control of plasticity and memory. Removing PNNs reactivates plasticity and restores memory in models of Alzheimer's disease and ageing. Their actions depend on the glycosaminoglycan (GAG) chains of CS proteoglycans, which are mainly sulfated in the 4 (C4S) or 6 (C6S) positions. While C4S is inhibitory, C6S is more permissive to axon growth, regeneration and plasticity. C6S decreases during critical period closure. We asked whether there is a late change in CS-GAG sulfation associated with memory loss in aged rats. Immunohistochemistry revealed a progressive increase in C4S and decrease in C6S from 3 to 18 months. GAGs extracted from brain PNNs showed a large reduction in C6S at 12 and 18 months, increasing the C4S/C6S ratio. There was no significant change in mRNA levels of the chondroitin sulfotransferases. PNN GAGs were more inhibitory to axon growth than those from the diffuse extracellular matrix. The 18-month PNN GAGs were more inhibitory than 3-month PNN GAGs. We suggest that the change in PNN GAG sulfation in aged brains renders the PNNs more inhibitory, which lead to a decrease in plasticity and adversely affect memory.
Keywords: plasticity; sulfation; Animals; Proteoglycans; Memory Disorders; glycosaminoglycans; nervová síť; Sulfotransferases; Aging; proteoglykany; Nerve Net; poruchy paměti; messenger RNA; mozek; Neurites; neurity; RNA, Messenger; perineuronal net; regulace genové exprese; Brain; Cell Extracts; stárnutí; krysa rodu Rattus; sulfotransferasy; Gene Expression Regulation; zvířata; Rats; buněčné extrakty; aging